Empowerment of Songket Woven Craftsmen: Qualitative Study of Creative Economy in Sukarara Village, Indonesia - Edhu Bagas Tantawi; I Wayan Suteja; Ihyana Hulfa; Ida Nyoman Tri Darma Putra; Uwi Martayadi (Advances in Tourism Studies, 2023)
This qualitative study examines the potential of the creative economy in Sukarara Village, Indonesia, by empowering Songket woven fabric craftsmen in tourism. The research question is to explore how empowering Songket craftsmen in tourism can revive the industry and promote the creative economy in Sukarara Village. The study was conducted in Sukarara Village, Jonggat District, Central Lombok Regency, West Nusa Tenggara, and data was collected through interviews, observations, and documentation. The participants included Songket woven fabric craftsmen, traditional institution members, and local community members involved in tourism activities. The data collection techniques used were semi-structured interviews, open-ended interviews, participant observation, and document analysis. The study's findings reveal that tourism activities based on the creative economy in Sukarara Village include weaving Songket fabrics, studying motifs and production, traditional customs, marketing, and management. The community involvement in empowering the craftsmen includes developing traditional institutions, arts, cadet's corals, and weaving patents. The study highlights the practical implications of empowering Songket craftsmen in tourism, such as boosting the local economy and promoting cultural heritage. In conclusion, this study provides insights into how the creative economy can be harnessed through tourism to revive traditional crafts and promote community development